SSI-Integrated PjBL Model in Biodiversity Topics: Is it Effective for Increasing Students' Digital Literacy? - Maolida, Amanda Syifa; Purwianingsih, Widi; Rahman, Taufik (Faculty of Mathematics and Natural Sciences, Universitas Negeri Yogyakarta, 2024)
Educational institutions can utilize digital technology to engage students in various learning models. The presence of technology must be combined with 21st-century skills, including digital literacy. This research aims to determine the increase in digital literacy (communication and collaboration, critical thinking, ICT familiarity, data literacy, device security, dan personal security) of high school students in the application of project-based learning (PjBL) integrated with socio-scientific issues in biodiversity material. The method used in this research is the pre-experimental method with a one-group pre-test-post-test design. The population and sample are class X students from one of the high schools in Bandung City, consisting of 36 students. The instruments used consist of a questionnaire, observation sheets, and product assessment rubrics. The data obtained were analyzed using the paired sample t-test and the N-Gain analysis test with the help of the SPSS Ver program 25. The research results show an increase in students' digital literacy from the high category to the very high category with an N-Gain gain of 0.59 and being in the medium category. There has been an increase in digital literacy in each category, the highest increase was obtained by the ICT familiarity indicator (N-Gain=0.78) and the lowest was obtained by the personal security indicator (N-Gain=0.31). The digital literacy aspect of the digital handbook product created by students received an average score of 86.75% and was in the very high category.